Strengthening collaborations at the public health system–academic interface: a call to action - Di Ruggiero, Erica (Can J Public Health, 2020)
In Canada and globally, the COVID-19 pandemic has highlighted the importance of reliable and responsive public health systems. The pandemic has required decisive leadership and collaboration across all sectors of society informed by the best available evidence. In this commentary, we argue that in order to create a robust public health system equipped to address current and future public health challenges, we must prioritize and invest in stronger relationships between public health practice and academia. We briefly review key recommendations following the SARS outbreak, particularly those calling for stronger linkages between public health academia and practice settings in Canada. We then propose key actions for strengthening these linkages. Echoing other COVID-19-related calls, which request long-term reinvestment in public health education and training, we recommend the following actions: (1) Improve collaboration between education programs and public health agencies to address system needs (e.g., surge capacity) and persisting health inequities; (2) Fund a pan-Canadian public health training initiative that builds on a renewed set of public health competencies to address priority training needs (e.g., equity-oriented leadership); and (3) Prepare a cadre of certified public health leaders who can progress along public health career pathways, including those already in practice.